2021
DOI: 10.1007/s00894-021-04778-1
|View full text |Cite
|
Sign up to set email alerts
|

Radical scavenger competition of alizarin and curcumin: a mechanistic DFT study on antioxidant activity

Abstract: In vivo hydroxyl, peroxyl, and superoxide free radicals caused by oxidative stress can be toxic to molecules that are essential for the human body. However, there are natural compounds that can decrease the amount of these harmful species. In this work, we are focusing on two well-known compounds, alizarin (red) and curcumin, to study their interactions with these small radicals for a comparison between a rigid and a flexible structure. We made a mechanistic study and found the major and minor degradation prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 57 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Regarding the rearrangement of the less stable OH‐adduct, the most plausible pathway is the cleavage of CC bond leading to the ring opening process. The ring opening process leads to the formation of biradical type of species which eventually stabilizes after reacting with another available • OH radical and finally forming ketonic analogues similar to the degradation products observed in the • OH radical reaction with alizarin and curcumin [65].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the rearrangement of the less stable OH‐adduct, the most plausible pathway is the cleavage of CC bond leading to the ring opening process. The ring opening process leads to the formation of biradical type of species which eventually stabilizes after reacting with another available • OH radical and finally forming ketonic analogues similar to the degradation products observed in the • OH radical reaction with alizarin and curcumin [65].…”
Section: Resultsmentioning
confidence: 99%
“…These results were then compared with IEFPCM solvation model and can be seen in the supplementary information (Table S1). Recently, Sadatsharifi & Purgel have also performed a detail comparison between these two solvation models in the hydroxyl, peroxyl, and superoxide free radicals reaction with alizarin and curcumin [65].…”
Section: Resultsmentioning
confidence: 99%
“…Both the keto-enol and phenolic group of Cur are thought to be the site responsible for radical scavenging, and other groups have suggested that hydrogen cleavage is the preferred ROS interaction mechanism of Cur. 52 In clinical trials, Cur is shown to increase total antioxidant capacity (TAC) and decrease malondialdehyde. 53 It also affects energy metabolism and increases overall ROS accumulation in SiHa cervical cancer cells resulting in increased autophagy and G2/M phase cell cycle arrest.…”
Section: Curcumin In Cancer Therapymentioning
confidence: 99%
“…Curcumin (CUR), a polyphenolic compound derived from the roots and stems of the curcuma plant (Gong et al, 2021;Jabbar et al, 2023), exhibits potent anti-inflammatory and antioxidant properties (Peng et al, 2021). Notably, CUR demonstrates robust free radical scavenging activity when compared to natural extracts like anthocyanins and β-carotene (Sadatsharifi and Purgel, 2021), suggesting its superior antioxidant efficacy over vitamins. In addition to scavenging reactive oxygen species and reactive nitrogen, CUR also elicits the upregulation of antioxidant enzymes (Guo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%